The anthropology of music: contemporary theoretical perspectives - Ivan Kovačević (University of Belgrade, 2016)
The anthropological study of music focuses on meanings which music hah and produces in a specific sociocultural context. Preferences toward a certain genre of music are tightly linked to the preference of certain cultural values, so music represents an important factor of identification in everyday life. In Serbian ethnology and anthropology music was long viewed as part of Serbian traditional culture, so the interests of researchers focused on “traditional music”. In the 1980’s first papers analyzing music which went outside the traditional frameworks appeared (new folk music – turbofolk), and this tendency has increased in the last ten years.